Percutaneous Hepatobiliary Endoscopy in the Interventional Radiology Suite - Anderson, Drew; Plotnik, Adam N.; Chick, Jeffrey Forris Beecham; Srinivasa, Ravi N. (Digestive Disease Interventions, 2020)
Percutaneous transhepatic choledochoscopy and cholecystoscopy have a growing place in the interventional radiology suite. Patients with indwelling tubes who may have once been left with limited options for stone extraction, targeted biopsy, and/or chronic biliary stricture can now have comprehensive care of their disease process by an interventional radiologist. There are a variety of low-profile and large-profile devices available in the hospital that can be repurposed for use in the biliary system and gallbladder. In many situations, these tools can be used to render patients with limited transoral endoscopic options and chronic indwelling tubes, tube free. This article provides an introduction to biliary endoscopy and cholecystoscopy and their role for the interventional radiologist.
Keywords: percutaneous endoscopy; biliary endoscopy; cholecystoscopy; choledochoscopy; lithotripsy; biliary stricture; laser